Ultra-Processed Foods, Diet Quality and Human Health - Dinu, Monica; Martini, Daniela (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The increase in the volume of industrially processed products in the global food supply has coincided with an increasing prevalence of obesity and non-communicable diseases in many countries, suggesting that ultra-processed food consumption may be detrimental for human health. However, studies are still limited and underline the need to better understand the main determinants of their consumption and the mechanisms that may explain the associations between these products and human health. This Special Issue collected new studies investigating the relationship between the consumption of ultra-processed foods, diet quality and human health, including those aiming to: Develop new tools to better determine the rate of consumption of ultra-processed foods in the population; Investigate the rate of consumption of ultra-processed foods in different subgroups of the population, including subjects following different dietary patterns; Analyse the relationship between the consumption of ultra-processed foods and markers of health status; Explore possible mechanisms behind associations between the consumption of processed foods and health By providing up-to-date assessments of ultra-processed foods consumption and health implications, these reports will contribute to understanding if future public health nutrition policies are needed.